Analisis Faktor Pendorong Peluang Partisipasi Perempuan Dalam Pengembangan Pariwisata Perbatasan di Entikong - Meri Sahrina Daema Nuryati (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2020)
ABSTRACT Women’s involvement in various fields has always been an interesting subjects for study, including its participation in tourism activity in the Entikong Border Post. The development of the Entikong Border Post as one of the tourist destinations known as the Border Tourism or Cross-Border Tourism is considered a great opportunity by the Indonesian government as one of the driving factors in improving the economy and welfare of the people around the border. The development of border tourism destinations has an influence on the involvement of women in the accommodation sector. The purpose of this study was to examine the forms of women’s participation in Entikong border tourism activity, as well as the factors that influence women’s participation in border tourism activity in Entikong, especially in the accommodation sector. The method used in this research was descriptive qualitative method with ethnographic method approach through library research, involved observation, interview, and documentation, as well as data analysis using domain analysis, taxonomic analysis, and componential analysis. Factors that encourage such participation are gender equality, benefits, and support from various parties such as family, customs, norms, and culture. Keyword: women participation; gender equality, culture